Pertumbuhan dan Produksi Habbatussauda (Nigella sativa L.) di Tiga Ketinggian di Indonesia - ,, Herlina; Aziz, Sandra Arifin; Kurniawati, Ani; Nur Faridah, dan Didah (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
ABSTRACTBlack cumin is an annual medicinal aromatic plant, cultivated mainly in mediteranean regions with low temperature (under 20 °C). The suitable planting area in the tropic for black cumin need to be studied. The aim of this study was to study the growth and production of black cumin in three altitudes of Indonesia tropical region. The experiment was conducted from June to October 2015 at Bogor Agricultural University experimental station in Leuwikopo, Dramaga (06o56’S, 106o73’E, 220 masl); Sukamantri, Ciapus (06o61’S, 106o78’E, 560 masl); and Sari Alam Medicinal Plant Garden in Ciwidey, Bandung (07o09’S, 107o50’E, 1,280 masl as control). This experiment used a nested design with two factors, i.e. altitudes (220, 560, 1,280 masl) and accesions (India, Kuwait). The variable studied were plant height, leaf area, leaf area index, leaf thickness, capsules per plant, seed per capsule, weight of 1,000 seeds, seeds per plant, and weight of seed per plant. Data was analyzed with compare means difference between low, middle altitude and high altitude as a control (1,280 masl) with t-student test. The result showed black cumin India and Kuwait accessions can be cultivated at low and middle altitude Indonesia tropical region. Plant height of India and Kuwait accession decrease 37.1 and 46.6% at 560 masl; 21.1 and 24.4% at 220 masl respectively, and yield decrease 26.9 and 59.4% at 560 masl and 44.5 and 63.9% at 220 masl, respectively.Keywords: black cumin, elevation variation, growth and production character